(untitled) (Journal Of Educational and Psychological Researches, 2011)
The aim of the research to show the direction of kindergarten‘s headmasters with students and know the educational technique used by the teachers with students inside kindergarten , also to know the differences of headmasters directions towards these technique according to changing of social state (married , unmarried ) and age state (30-38) (39-47) (48-56) . Also shows the sign among the direction of head masters and educational technique used by teachers with student, where as the importance of this research shows the importance of the kindergarten stage and the importance of management . The role of headmaster and teacher consider the relationship between them and the mother so that this origin direction shows the success of this mission connect of providing the principle conditions of kindergarten‘s management to choice the good simples then preparing them in scientific way to success in this mission , but the researcher show the research‘s problem from exploration study between headmaster and teacher and from these simple experiments of researcher after using (T) test with two samples , Berson‘s coefficient connect and (T)test with one sample . the researcher reach to :- The headmasters have positive direction towards the educational technique used by the teacher towards student also there is no clear point towards the social state (married , un married ) , but there is clear point to the age state (30-38) (39-47) (48-56) and the favorite is (30-38) For the educational style the teacher used forgiven style more than other one . so the researcher reach to suggestion used to benefit of educational activity inside and outside kindergarten